Tannins and copper sulphate as antimicrobial agents to prevent contamination of Posidonia oceanica seedling culture for restoration purposes - Alagna, Adriana; Giacalone, Vincenzo Maximiliano; Zenone, Arturo; Martinez, Marco; D’Anna, Giovanni; Buffa, Gaspare; Cavalca, Caterina Jessica; Poli, Anna; Varese, Giovanna Cristina; Prigione, Valeria Paola; Badalamenti, Fabio (Frontiers in Plant Science, 2024)
Seed-based restoration methods are increasingly recognized as a relevant tool contributing to halt and reverse the loss of seagrass meadows while providing genetic and evolutionary benefit for the conservation of these habitats. Ad-hoc protocols aimed at maximizing the survival of plantlets obtained from seeds in cultivation systems are therefore required. Previous trials of seedling culture of Posidonia oceanica, the dominant seagrass of the Mediterranean Sea, recorded up to 40% loss due to mould development. In this study we aim to (i) identify the putative causal agents of seed decay and (ii) test the efficacy of copper sulphate (0.2 and 2 ppm) and of tannin-based products derived from chestnut, tara and quebracho in reducing seed and seedling decay, while assessing possible phytotoxic effects on plant development. Halophytophthora lusitanica, H. thermoambigua and a putative new Halophytophtora species were identified as possible causal agents of seed loss. The antimicrobial agents (copper and tannins) reduced seed contamination by 20%, although copper sulphate at 2 ppm strongly inhibited the root growth. Among tannins, chestnut and tara reduced seeds germination by up to 75% and decreased shoot and root development, while quebracho showed a less severe phytotoxic effect. The use of copper sulphate at 0.2 ppm is therefore recommended to prevent P. oceanica seedling loss in culture facilities since it reduces seed contamination with no phytotoxic effects. Our results contribute to improving the seedling culture of one the key species of the Mediterranean Sea, increasing propagule availability for restoration purposes.